Design Thinking Traits of Teachers Immersed in the Orange Economy - Campodónico-Centurión, Silvia (2019)
This research is of a comparative descriptive type and was carried out with the objective of identifying if the professors of higher education of careers oriented to the orange economy present design thinking traits, as well as the methodologies they use to innovate both in the exercise of their profession as for its pedagogical work, in addition, to compare if the presence of these traits obeys or not to the characteristics of the teachers. As a sample, 232 teachers from the Toulouse Lautrec School of Higher Education were taken, who responded to a scale of design thinking features, resulting in information search, integrative thinking, optimism and collaboration traits being more present in those teachers who They have as a significant differentiating characteristic to exercise their profession in independent jobs and have more than 10 years of exercising their profession and teaching work.